Influence of dialysis membrane composition on plasma bisphenol A levels during online hemodiafiltration - Mas, Sebastian; Bosch Panadero, Enrique; Abaigar, Pedro; Camarero, Vanesa; Mahillo Fernández, Ignacio; Civantos, Esther; Sánchez Ospina, Didier; Ruiz Priego, Alberto; Egido, Jesús; Ortiz, Alberto; González Parra, Emilio (My University, 2018)
Introduction Bisphenol A (BPA) is an ubiquitous environmental toxin that is also found in dialyzers. Online hemodiafiltration (OL-HDF) more efficiently clears high molecular weight molecules, and this may improve BPA clearance. However, the BPA contents of dialysis membranes may be a source of BPA loading during OL-HDF. Methods A prospective study assessed plasma BPA levels in OL-HDF patients using BPA-free (poly nephron) or BPA-containing (polysulfone) dialyzers in a crossover design with two arms, after a run-in OL-HDF period of at least 6 months with the same membrane: 31 patients on polynephron at baseline were switched to polysulfone membranes for 3 months (polyne phron-to-polysulfone) and 29 patients on polysulfone were switched to polynephron for 3 months (polysulfone-to-polynephron). Results After a run-in OL-HDF period of at least 6 months with the same membrane, baseline pre dialysis BPA was lower in patients on polynephron (8.79±7.97 ng/ml) than in those on poly sulfone (23.42±20.38 ng/mL, p<0.01), but still higher than in healthy controls (<2 ng/mL). After 3 months of polynephron-to-polysulfone switch, BPA was unchanged (8.98±7.88 to 11.14±15.98 ng/mL, ns) while it decreased on the polysulfone-to-polynephron group (23.42±20.38 to 11.41±12.38 ng/mL, p<0.01).